A Recent Update of Ixekizumab in Moderate to Severe Plaque Psoriasis (International Journal of Food and Nutritional Sciences, 2022)
Psoriasis is a chronic skin disease affecting millions of people globally. The most common type of psoriasis is plaque psoriasis. Currently FDA-approved Ixekizumab for the treatment of moderate to severe plaque psoriasis in adults. Ixekizumab is monoclonal antibody with high affinity. It selectively targets IL-17A and is indicated for the treatment. It is phase III of clinical trials and three phases of phase III clinical trials were conducted for safety and efficacy, namely UNCOVER I, UNCOVER II and UNCOVER III. Previously conducted various study was reviewed and analyzed in this study. Ixekizumab has proved to be safe and efficacious in the treatment of moderate to severe plaque psoriasis.